Novel ic thermometer placed in the uterotubal junction to measure bovine uterine temperature. technical note - Roa, Noris; Kamimur, Shunichi; Hamana, Katsumi; Morita, Kazuo; Shibata, Ikuo; Linares, Tiburcio (Revista Científica de la Facultad de Ciencias Veterinarias)
Physio-environments in bovine uterus have not been adequately reported due to the limitations in methodology. The objective of the study was to measure bovine uterine temperature (UT) by a novel IC thermometer (IC). Data was compared with conventional rectal (RT) and vaginal temperature (VT). IC is a chip housed in a button shaped stainless steel enclosure, 15 mm in length, 5mm in width with a range of +15 to +46°C in 0.125°C increments. It was calibrated with a standard mercury thermometer, and was also correlated with a rectal thermometer installed with a sensor probe (0.1°C precision). UT was measured in 20 min intervals for 4 weeks, while RT and VT were measured every 4 hr. Eleven Japanese Black cows, 8 in the summer and 3 in the winter were subjected to caesarian section (CS). By trans-lumbar laparotomy, IC was installing in the left uterine horn proximate to the uterotubal junction during CS. After recording for 4 weeks, IC was removed by 2nd CS and mounted on the chip reader in the PC. The accumulated data were analyzed by ANOVA for repeated measures. Ambient temperature (AT) was simultaneously recorded. In 5 cows, blood was daily collected for hormonal (estradiol) assay and underwent ultrasonography to monitor ovarian dynamics. Temperature after operation was temporarily elevated for 4 days (0.14°C) and excluded. Averages in UT, RT and VT in the summer (AT: 28.76°C) were 38.57 Ó 0.23°C, 38.67 Ó 0.23°C, 38.60 Ó 0.35°C, and those in the winter (AT: 14.46°C) were 38.63 Ó 0.21°C, 38.68 Ó 0.21°C, 38.67 Ó 0.20°C, respectively. UT was significantly lower than RT or VT, and UT in the summer was lower than in the winter (P menor 0.01). Diurnal rhythm was observed at all three temperatures, lowest at 08:00 and highest at 20:00 h. Upon ovulation, UT in the luteal phase was significantly higher (38.61 Ó 0.20°C) than in the follicular phase (38.51 Ó 0.22°C, P menor 0.01), whereas no difference was observed in RT or VT. In conclusion, IC placed in the uterotubal junction successfully measured UT and detected diurnal rhythm. UT fluctuation was stable, but showed a hyperthermia in luteal phase. It appear that IC device can be use to monitory uterine temperature during estrus cycle and probably in some other reproductive physiology processes in cows.